Comparing Efficiency of Public Universities among European Countries: Different Incentives Lead to Different Performances. (23rd January 2015) - Agasisti, Tommaso; Haelermans, Carla
Abstract: This paper analyses the relationship between the public funding systems of higher education in Italy and the Netherlands and their universities' performances. Empirically, an efficiency analysis on 13 Dutch and 58 Italian public universities is conducted. The findings show that the relative efficiency of Italian and Dutch universities is strongly influenced by the policy perspective adopted. If the goal is to realise the European goals and minimise resources employed for obtaining a high number of graduates, Dutch universities turn out to be more efficient. However, Italian universities are much more efficient if the priority is to minimise the costs for a given level of activity, such as number of students.